The Influence of Entrepreneurial Competence and Succession Planning on the Sustainability of Family-Owned MSMEs with Organizational Commitment as a Mediating Variable - Frimayasa, Agtovia; Purnama, Yanthy Herawaty (Sean Institute, 2025)
This study aims to examine the influence of entrepreneurial competence and succession planning on the sustainability of family-owned MSMEs, with organizational commitment as a mediating variable. Using a quantitative explanatory approach, data were collected through structured questionnaires distributed to 50 family business owners in Rempoa, South Tangerang. The data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS tool. The results show that both entrepreneurial competence and succession planning have a positive and significant effect on business sustainability, both directly and indirectly through organizational commitment. Organizational commitment plays a key mediating role, bridging internal capabilities and strategic succession with long-term business continuity. The findings highlight the importance of strengthening internal organizational aspects, such as loyalty and shared responsibility, to ensure intergenerational sustainability of family MSMEs. This research provides theoretical insights and practical recommendations for MSME actors and policymakers in designing training and succession planning programs.